Being @ : a thesis presented in partial fulfilment of the requirements for the degree of Master of Design at Massey University, Wellington, New Zealand - Foster, Stuart (Massey University, 2006)
In the past decade, the rapid proliferation of computers and networked communication technologies has offered the opportunity to experience a new kind of space, a space that is real but immaterial, where the imaginary can be shown without the need or support of concrete matter. We are entering a new era in our everyday interaction with the world, "an era of electronically extended bodies living at intersection points of the physical and virtual worlds" (Mitchell, 1995, p.24). This thesis operates in an unstable zone that bridges these two realms. The research applies theoretical findings into the production of an experiential system, a system that operates across the corporeality of the physical environment and the metaphysical realm of a cyber-spatial environment. The research proposes that Cyberspace can be conceptualised as a representation of spatial experience figured upon 'being-in-the-world' (a phenomenological paradigm). It aims to locate, define and operate within and across the liminal zone, the threshold between corporeal space experience and computer meditated space. This zone, in terms of spatiality, is framed as the experience of the interface, the dematerialising horizon of human being and place (Perella, 1995). Interface becomes the point of departure from corporeal into the metaphysical dimensions of cyber-spatiality.
Extra material images and video held with print copy in Library
Keywords: Interior decoration; Space (Architecture) -- Planning; Data processing; Computer-aided design